Concept of green marketing in environment conservation: A Literature review - Osiako, Peter Onyonje; Wikurendra, Edza Aria; Abdeljawad, Nour Salah (Universitas Nahdlatul Ulama Surabaya, 2022)
The concept of green marketing mix is as well as the conventional marketing mix refers to the satisfaction of customer needs, wants, and desires related to the maintenance and preservation of the environment. Consumers interest in environmental care creates opportunities for companies to apply green marketing and to increase sales. Green marketing becomes an alternative strategy helps the company's image, adds value to the company's business, even consumers demand green choices and will to pay higher prices. The marketing strategy includes the company's external and internal factors. The marketing mix strategy is the basic idea and generic function of marketing which consists of product, price, place, and promotion elements to shape the occurrence of sales. Developing the concept of green marketing mix (green marketing mix) is inseparable from the traditional 4P concepts (product, price, place, promotion), except a number of additional component are closely related to the intent of green marketing itself and other very influential things. The implementation of a green marketing strategy requires a fundamental, comprehensive and integrated approach in all functional aspects of marketing, including the overall marketing mix, such as product design, pricing, location and promotion.